(untitled) (Research, Society and Development, 2024)
In small animal veterinary clinics, Acute Kidney Injury (AKI) in felines is a common illness. Kidney disease affects one in every three cats over twelve years of age, being one of the biggest causes of death in this species. ARF is a clinical syndrome caused by kidney damage, characterized by an increase in serum concentrations of urea and creatinine, causing the animal to present a series of clinical signs, such as inappetence, vomiting and stomatitis, which can even lead to death. Therefore, it is important for the veterinarian to identify and apply the protocol that best suits a patient with ARF. In the case of felines, ARF becomes even more worrying, due to the anatomical particularities of the species. In this sense, the aim of this work is to review the literature on the causes that lead to this disorder, point out the clinical signs of this disease and highlight some prevention guidelines for ARF in cats.